ENGLISH TEACHING MATERIALS DURING GLOBAL PANDEMIC: A SURVEY ON ONLINE LEARNING AT VOCATIONAL SCHOOLS IN LAMPUNG - Nyanuar Algiovan; Ahmad Subhan Roza (English Education Department, 2020)
Coronavirus spread around the world affects many things. Education is one of many affected sectors. Indonesia is a country which mostly effected by Coronavirus. Thousand students throughout the nations left the schools and start adapting a distance learning. It forces all teachers and students to learn and adapt to online learning. English teaching materials play a role in providing students with contextual knowledge. By far, English learning materials have only been inserted about moral values and other values. Though, English teaching materials are considered possible to be a means of learning students on issues related to disaster education. This research investigates the media platforms and materials used by English teachers during the pandemic in vocational high schools in East Lampung. The study used Cross-sectional Designs Survey with questionnaires as data collection techniques. Participants of 27 vocational schools of English teachers. The survey was done in the beginning of first semester. The aims are to know the materials and platforms which are used also to see the teachers’ understanding regarding the disaster education during a global pandemic. The findings gained are (1) Most teachers use WhatsApp in providing teaching materials. (2) The majority of respondents were aware of disaster education but only limited to COVID issues. (3) English teachers have not understood the overall disaster education. There are three main suggestions of this current work : Incorporating of teaching materials integrated with disaster education, environmental, and natural issues. Maximizing the fore on the application of online learning. Enhancing of disaster education at all levels of education.